Aceleración y descomposición de sustratos orgánicos en la elaboración de compost mediante el uso de diferentes sustancias (azúcar, melaza, caña de azúcar). - Mayorga Ruíz, Esther Mariela (2016)
The present investigation was carried out in order to evaluate the effect of different substances additional to the compost to accelerate their decomposition. The experiment was carried out at the Experimental Farm "La María" of Quevedo State Technical University, located at Km 7.5 of the Via Quevedo - El Empalme. A completely randomized design was used with four treatments in four replicates, being the treatments: sugar, molasses, sugarcane juice and a control. The treatment with molasses decreased in six days the period of decomposition in relation to the control, that is to say in 9.68%. The results of the temperature evaluations at the beginning and at the end of the trial did not show any significant differences, evidencing that the treatment with molasses experienced a greater drop in temperature with 8.7 ° C. The moisture content of the mounds with the application of the different substances added, did not register significant differences, registering averages that oscillated between 56.5 and 59.0%. Applying molasses obtained a lower final weight with 39.3 kg, reflecting a weight loss of 10.8 kg, which can be attributed to a better decomposition process of organic matter. The pH levels of the mounds of compost with the application of different substances did not differ significantly, reflecting a pH between 8.0 and 8.4. The nutritional content of compost mounds with the addition of the treatments under study did not differ significantly. The treatment with molasses represents a great option since it facilitates the obtaining of compost of better characteristics.